FISCAL AND MONETARY POLICY SYNERGY IN THE FRAMEWORK OF ISLAMIC ECONOMICS: SOLUTIONS TO MACROECONOMIC STABILITY CHALLENGES - Salsabila, Bunga; Nurkhofifaturohma, Mita; Muslimah, Rafika Hauli; Rosviana, Mohammad Irfan (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2025)
The monetary policy implemented in Indonesia affects the country's economic growth, especially when viewed from the perspective of Islamic economics. This study explores that monetary policies such as interest rate regulation, sharia monetary instruments, and financial stability can be aligned with Islamic economic principles that emphasize justice, mutual benefit, and freedom from riba (interest). The purpose of this study is to analyze the issue of the influence of monetary policy on Indonesia's economic growth which will be studied from an Islamic perspective. The method of writing this article uses a qualitative approach that is closely related to theoretical writings and other references related to the laws, cultures, and norms that apply in the social situation being studied. The results of this study show that Islamic monetary policy prohibits riba and uses interest-free instruments to achieve economic prosperity and stability. This policy is divided into expansive and contractive, with six elements of sharia that must be met. With a comprehensive and balanced approach, Islamic monetary policy is expected to promote sustainable and inclusive economic growth, address inequality, and ensure that economic benefits can be felt by all levels of society.